Sexual Harassment and Victimization from Four Other Types of Interpersonal Aggression in Ghana: A Cycle of Victimization - Farida Anwar; Karin Osterman; Jasmine Afari-Korkor; Kaj Bjorkqvist Kaj Bjorkqvist (Universitas Ahmad Dahlan, 2020)
The aim of the study was to investigate victimization from sexual harassment, and level of emotional distress due to it, are associated with four other types of victimization. A questionnaire was completed by 280 female university students and lecturers in Ghana. The mean age was 26.7 years (SD = 6.2). The questionnaire included scales for measuring frequency of sexual harassment, emotional distress due to sexual harassment, physical punishment during childhood, victimization from peer aggression at school, and victimization from intimate partner aggression. Respondents who were more than average victimized from sexual harassment scored significantly higher on physical punishment during childhood, victimization from peer aggression at school (revictimization), and victimization from intimate partner aggression (multiple victimization).When frequency of sexual harassment was controlled for, emotional distress caused by sexual harassment correlated positively with victimization from peer aggression at school, and victimization from verbal intimate partner aggression, thus suggesting sensitization to aggression. Victimization from sexual harassment was associated with higher levels of both previous and simultaneous victimization from other types of aggression, thus corroborating the principles of both revictimization and multiple victimization. The finding does not suggest that sexual harassment in all cases is associated with other types of victimization.Keywords: sexual harassment, revictimization, emotional distress, Ghana